Kebermaknaan Hidup dalam Falsafah Hidup Banjar “Waja Sampai Kaputing”: Studi Fenomenologis pada Mahasiswa - Meininda Rhivent Norhidayah; Diana Rahmasari (Universitas Airlangga, 2026)
Research on the meaning of life among college students in Indonesia generally focuses on religiosity and psychological well-being, while studies linking it to local cultural values such as the Banjar philosophy of Waja Sampai Kaputing remain limited. Local cultural values can serve as sources of psychological strength amid modernization. This study aims to examine how Banjar ethnic students interpret life through this philosophy. A qualitative phenomenological approach was used involving five students in Banjarmasin. Data were collected through semistructured interviews and social media observation, then analyzed using Interpretative Phenomenological Analysis (IPA). The results indicate that Waja Sampai Kaputing is interpreted as a source of resilience, cultural identity, and a guide for social responsibility. Values such as hard work, perseverance, and persistence strengthen resilience in facing academic and social pressures. Social engagement enriches life meaning. This study confirms that local cultural values play a central role in shaping meaning among younger generations.